UMI-77 targets MCL-1 to activate mitophagy and ameliorate periodontitis in mice - Dalei Sun; Shu Ouyang; Xiaoxuan Xu; Jingjing Yan; Heqian Wang; Chenkai Lan; Wubin Ouyang; Liangjun Zhong; Jun Lin (Immunobiology)
Objective: To investigate the therapeutic and ameliorative effects of the Myeloid Cell Leukemia 1 protein (MCL-1) inhibitor UMI-77 on experimental murine periodontitis via mitophagy activation, with a focus on comparing administration routes (local/intraperitoneal) and doses (high/low/combined). Methods: A ligature-induced periodontitis model was established in 54 male C57BL/6 J mice, randomized into 9 groups (n = 6 per group): normal control (Group Aa), periodontitis model (Group Ab), positive control (Group Ac, local minocycline), local PBS control (Group Ad), intraperitoneal PBS control (Group Ae), local high-dose UMI-77 (Group Ba, 2 mg/kg), local low-dose UMI-77 (Group Bb, 1 mg/kg), intraperitoneal UMI-77 (Group Ca, 2 mg/kg), and combined intraperitoneal UMI-77 + local minocycline (Group Cb, 2 mg/kg + standard minocycline regimen). Outcomes included periodontal bleeding on probing (BOP), alveolar bone resorption via micro-CT, histopathological analysis (HE/methylene blue staining), MCL-1 expression (Western blot), autolysosome detection (transmission electron microscopy, TEM), and systemic organ safety (HE staining). Results: All UMI-77 treatment groups exhibited significant amelioration of periodontal inflammation and bone resorption compared to the model group (Ab, p < 0.0001). Local high-dose UMI-77 (Group Ba) demonstrated the most potent efficacy, reducing BOP by 76 % (0.67 ± 0.5 vs. Ab: 2.8 ± 0.4, p < 0.001) and cementoenamel junction–alveolar bone crest distance by 48.7 % (0.20 ± 0.04 mm vs. Ab: 0.41 ± 0.05 mm, p < 0.0001), outperforming the positive control (Group Ac, BOP: 2.17 ± 0.4, p < 0.001). Histological analysis showed reduced inflammatory cell infiltration and organized periodontal fibers in Group Ba. Western blot confirmed downregulation of MCL-1 expression to near-normal levels in Group Ba, while TEM detected autolysosomes in both Group Ba and Group Ca, indicating mitophagy activation. Systemic safety assessments revealed only mild grade 1 cardiac septal thickening in Group Ba and transient splenic lymphocyte elevation in Group Ca, with no severe organ toxicity. Conclusion: UMI-77 exerts significant therapeutic and ameliorative effects against periodontitis in mice, with local high-dose administration (Group Ba) demonstrating optimal efficacy. Intraperitoneal UMI-77 combined with local minocycline (Group Cb) achieved comparable outcomes to high-dose local UMI-77, highlighting potential combinatorial strategies. These findings establish UMI-77 as a promising agent for periodontitis treatment via MCL-1-targeted mitophagy activation. Clinical significance: UMI-77, especially with local high-dose administration, offers a new, potentially effective and safe approach for periodontitis treatment, holding great promise for clinical translation.